IDP detection in Earth environment: Prediction of plasma capture efficiency and detector response to high-energy particles. (June 2022) - Pabari, J.P.; Nambiar, S.; Singh, R.K.; Bhardwaj, Anil; Lad, K.A.; Acharyya, K.; Jakhariya, J.M.; Jitarwal, S.; Rashmi,; Sheel, V.
Abstract: Interplanetary dust particles exist everywhere in the space between any two planets. These particles are originated from sources like Asteroid belt, Kuiper belt or comets and they evolve through their orbital paths. Various planets like Mars, Earth or Venus may capture such particles during their inward travel. Flux of dust particles at a given planet is important to understand total inflow of material and also, metal ion layers formed in atmosphere due to ablation. Using past observations around Earth and an existing flux model, a power law model is suggested for incoming particle flux at Earth. Expected particle number density around Earth is presented based on the suggested model. To detect such dust particles, an impact ionization dust detector is proposed for planetary application and it is under development at Physical Research Laboratory. A dust impact on detector target produces charge carriers, which are captured by voltage biased electrodes for further processing. For the dust detector, bias optimization is worthwhile to reduce resources required on board a satellite. In this regard, prediction of plasma capture efficiency is presented here using SIMION software, to get first hand estimate of detector performance. In addition, the detector receives high-energy solar wind particles and Galactic Cosmic Rays in space, along with the dust. Therefore, understanding detector response to high-energy particles is utmost important during normal solar conditions and also during SEP events. Through an extensive simulation using Geant4 software and ACE, GOES as well as SPENVIS datasets, it is found that high-energy particles act as noise for the detector in electron channel only. The dust impact can easily be identified from the background noise using the signal coincidence. The results could be useful to understand dust flux at Earth and also for the detector optimization. Highlights: A power law model for incoming dust flux at Earth is suggested. An upper limit of dust density around Earth is found to be 10 -4 ​#/m 3, on an average. SIMION results give first-hand estimate of plasma capture efficiency of detector to be 26 % for an optimum bias of 200 V. ACE, GOES and SPENVIS data are analysed to know real scenario in space. Geant4 results show noise in electron channel only. Signal coincidence can uniquely identify a dust impact in the presence of noise.